Powder for laminate molding, and laminate molded body

By using metal particle powder coated with an amino group or an epoxy coupling agent compound and forming a coating by heating, the problem of slow penetration of the adhesive solution in the adhesive spraying method is solved, and the manufacturing speed and surface accuracy of the laminated molding body are improved.

CN119681259APending Publication Date: 2025-03-25SEIKO EPSON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411309575.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-22
Filing Date
2024-09-19
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the adhesive spraying method, it is difficult for the aqueous adhesive solution to penetrate into the powder layer quickly, resulting in a decrease in manufacturing speed and a decrease in surface accuracy.

Method used

The powder coated with metal particles from the coupling agent compound having an amino group or an epoxy group is used to form a coating film by heating to increase the permeability rate of the adhesive solution.

Benefits of technology

The rapid penetration of the aqueous adhesive solution in the powder layer is achieved, and the manufacturing speed and surface accuracy are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119681259A_ABST
    Figure CN119681259A_ABST
Patent Text Reader

Abstract

Provided are: a powder for laminate molding that, when supplied to a laminate molding method using an aqueous binder solution, makes it possible to efficiently produce a laminate molded body having high surface precision, said laminate molded body being capable of producing a metal sintered body having high surface precision by sintering; a powder for laminate molding, which is used in the production of a laminate molded body by a binder injection method, and which is characterized by comprising: metal particles; and a coating film which is provided on the surface of the metal particles, contains a compound derived from a coupling agent having an amino group or an epoxy group, and has a water permeation time of 10.00 seconds or less when 40 [mu] L of water is dropped into a powder layer formed by powder pressing at a relative density of 51%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to powder for laminated molding and a laminated molding body. Background Art

[0002] As a technique for molding three-dimensional objects, a layered molding method using metal powder has been popularized in recent years. As one of such layered molding methods, a binder spraying method is known.

[0003] Patent document 1 discloses a solid free-form manufacturing system, which uses inkjet printing technology to solidify the powder by injecting droplets of different volumes as droplets of an adhesive into a powder layer to produce an object. The method for manufacturing an object using such a system includes a step of injecting droplets of an adhesive, and thus can be regarded as a type of adhesive jetting method. According to such a system, by injecting droplets of different volumes, an object with a finished smooth surface can be manufactured.

[0004] Patent Document 1: Japanese Patent Application No. 2006-515813

[0005] In the binder spraying method, water-based liquid (water-based binder solution) is often used as the binder droplets. The water-based binder solution penetrates into the powder layer, thereby solidifying the portion.

[0006] However, depending on the surface state of the powder, the aqueous binder solution may not be able to quickly penetrate into the powder layer. In this case, the penetration takes time, so the supply speed of the aqueous binder solution is reduced or the penetration range becomes uneven. Thus, the manufacturing speed of the object (molded body) is reduced, and the surface accuracy of the manufactured object is reduced. Summary of the invention

[0007] The laminated modeling powder according to the application example of the present invention is used in the production of a laminated modeling body by a binder jetting method, and the laminated modeling powder comprises:

[0008] Metal particles; and

[0009] The coating is provided on the surface of the metal particles and contains a compound derived from a coupling agent having an amino group or an epoxy group,

[0010] When 40 μL of water was dropped onto a powder layer formed by compacting the powder to a relative density of 51%, the time required for the water to penetrate was 10.00 seconds or less.

[0011] The stacked structure according to the application example of the present invention has:

[0012] A powder for laminated molding according to an application example of the present invention; and

[0013] The binder binds the particles of the laminated modeling powder to each other. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a process diagram showing an example of a method for producing a stacked structure.

[0015] Figure 2 It is used to illustrate Figure 1 A diagram showing a method for manufacturing a stacked structure.

[0016] Figure 3 It is used to illustrate Figure 1 A diagram showing a method for manufacturing a stacked structure.

[0017] Figure 4 It is used to illustrate Figure 1 A diagram showing a method for manufacturing a stacked structure.

[0018] Figure 5 It is used to illustrate Figure 1 A diagram showing a method for manufacturing a stacked structure.

[0019] Figure 6 It is used to illustrate Figure 1 A diagram showing a method for manufacturing a stacked structure.

[0020] Figure 7 It is used to illustrate Figure 1 A diagram showing a method for manufacturing a stacked structure.

[0021] Figure 8 It is used to illustrate Figure 1 A diagram showing a method for manufacturing a stacked structure.

[0022] Fig. 9 It is used to illustrate Figure 1 A diagram showing a method for manufacturing a stacked structure.

[0023] Fig.10 It is used to illustrate Figure 1 A diagram showing a method for manufacturing a stacked structure.

[0024] Fig.11 It is a cross-sectional view schematically showing the powder for laminated modeling according to the embodiment.

[0025] Fig.12 This is an example of an infrared absorption spectrum obtained from the powder for laminated modeling when the powder for laminated modeling has an amino group.

[0026] Fig.13 This is an example of an infrared absorption spectrum obtained from the laminated modeling powder when the laminated modeling powder has an epoxy group.

[0027] Description of Reference Numerals

[0028] 1: laminated modeling powder; 2: laminated modeling device; 4: adhesive solution; 6: laminated modeling body; 11: metal particles; 12: coating; 13: surface covering particles; 21: device body; 22: powder supply elevator; 23: modeling table; 24: coater; 25: roller; 26: liquid supply unit; 31: powder layer; 41: adhesive layer; 60: forming area; 211: powder storage unit; 212: modeling unit; P1: peak P1; P2: peak P2; P3: peak P3; S102: powder layer forming process; S104: adhesive solution supply process; S106: repeating process. DETAILED DESCRIPTION

[0029] Hereinafter, preferred embodiments of the laminated molding powder and the laminated molding body of the present invention will be described in detail with reference to the accompanying drawings.

[0030] 1. Method for manufacturing a laminated body

[0031] First, an example of a method for producing a laminated modeling body using laminated modeling powder will be described.

[0032] Figure 1 This is a process diagram showing an example of a method for producing a stacked structure. Figures 2 to 10 They are used to illustrate Figure 1 FIG. 1 is a diagram of a method for manufacturing a stacked molding body. Figures 2 to 10 In the invention, the X-axis, Y-axis, and Z-axis are set as three mutually orthogonal axes. Each axis is indicated by an arrow, and the front end side is set as the "positive side" and the base end side is set as the "negative side". In the following description, in particular, the positive side of the Z-axis is set as the "upper side" and the negative side of the Z-axis is set as the "lower side". In addition, the two directions parallel to the X-axis are called the X-axis directions, the two directions parallel to the Y-axis are called the Y-axis directions, and the two directions parallel to the Z-axis are called the Z-axis directions.

[0033] Figures 1 to 10 The manufacturing method of the stacked molding body shown is a method of stacking molding method, namely a method called binder jetting method, such as Figure 1 As shown, there are a powder layer forming step S102, a binder solution supplying step S104, and a repeating step S106. The binder jetting method does not require a support structure for supporting the stacked molded body, and thus has the advantage of being able to produce a stacked molded body of a complex shape.

[0034] In the powder layer forming step S102, the modeling powder 1 is applied to form a powder layer 31. In the binder solution supplying step S104, the binder solution 4 is supplied to a predetermined area of ​​the powder layer 31 to bond the particles in the powder layer 31 to obtain a bonding layer 41. In the repetition step S106, the powder layer forming step S102 and the binder solution supplying step S104 are repeated once or more to obtain a bonding layer 41. Fig.10 The stacked shaped body 6 shown. The manufactured stacked shaped body 6 is subjected to a sintering process to become a metal sintered body. The shape of the stacked shaped body is reflected in the obtained metal sintered body, thereby making it possible to efficiently manufacture a metal sintered body of a complex shape. The following will explain each process in order.

[0035] 1.1.Layered modeling device

[0036] First, before describing the powder layer forming step S102 , the lamination molding device 2 will be described.

[0037] The stacking molding device 2 comprises: an apparatus body 21 having a powder storage section 211 and a molding section 212; a powder supply elevator 22 arranged in the powder storage section 211; a molding table 23 arranged in the molding section 212; and a coater 24, a roller 25 and a liquid supply section 26 movably arranged on the apparatus body 21.

[0038] The powder storage section 211 is provided in the apparatus body 21 and is a recessed section with an upper opening. The powder storage section 211 stores the layered molding powder 1. Then, an appropriate amount of the layered molding powder 1 stored in the powder storage section 211 is supplied to the molding section 212 by the coating machine 24.

[0039] A powder supply elevator 22 is disposed at the bottom of the powder storage section 211. The powder supply elevator 22 can move in the up-down direction while being loaded with the layered molding powder 1. By moving the powder supply elevator 22 upward, the layered molding powder 1 placed on the powder supply elevator 22 is pushed up and overflows from the powder storage section 211. Thus, the overflowed layered molding powder 1 can be moved to the molding section 212 side.

[0040] The molding section 212 is provided in the apparatus body 21 and is a recessed section with an upper opening. A molding table 23 is arranged inside the molding section 212. The molding powder 1 is applied in layers on the molding table 23 by a coating machine 24. In addition, the molding table 23 can be moved in the vertical direction in a state where the molding powder 1 is applied. By appropriately setting the height of the molding table 23, the amount of the molding powder 1 applied on the molding table 23 can be adjusted.

[0041] The coater 24 and the roller 25 extend in the Y-axis direction and can move in the X-axis direction from the powder storage section 211 to the molding section 212. The coater 24 can flatten and lay the laminated molding powder 1 in a layer by dragging the laminated molding powder 1. The roller 25 compresses the laminated molding powder 1 from above by rolling the flattened laminated molding powder 1.

[0042] The liquid supply unit 26 is composed of, for example, an inkjet head, a dispenser, etc., and can move in the X-axis direction and the Y-axis direction in the molding unit 212. In addition, the liquid supply unit 26 can supply a target amount of the binder solution 4 to a target position. In addition, the liquid supply unit 26 can also include a plurality of ejection nozzles in one inkjet head. In addition, the binder solution 4 can also be ejected from the plurality of ejection nozzles simultaneously or with a time difference.

[0043] 1.2. Powder layer formation process

[0044] Next, the powder layer forming step S102 using the above-mentioned layered molding device 2 is described. In the powder layer forming step S102, the layered molding powder 1 is laid on the molding table 23 to form a powder layer 31. Specifically, Figure 2 as well as Figure 3 As shown, the coating machine 24 is used to drag the layered molding powder 1 stored in the powder storage section 211 onto the molding table 23 and smooth it to a uniform thickness. Figure 4 The powder layer 31 shown. At this time, the upper surface of the molding table 23 is made lower than the upper end of the molding part 212, and the amount of descent is adjusted, thereby adjusting the thickness of the powder layer 31. In addition, as described later, the laminated molding powder 1 is a powder with excellent filling properties when flattened. Therefore, a powder layer 31 with a high filling rate can be obtained.

[0045] Next, while the powder layer 31 is compressed in the thickness direction by the roller 25, Figure 4 As shown, the roller 25 is moved in the X-axis direction. As a result, the filling rate of the layered modeling powder 1 in the powder layer 31 can be increased. In addition, the compression by the roller 25 can be performed as needed and can be omitted. In addition, the powder layer 31 can also be compressed by a unit different from the roller 25, such as a pressing plate.

[0046] 1.3. Binder solution supply process

[0047] In the binder solution supplying step S104, Figure 5 As shown, the binder solution 4 is supplied to the formation area 60 corresponding to the stacked molding body 6 to be molded in the powder layer 31 through the liquid supply unit 26. The binder solution 4 is a liquid containing a binder and a solvent or a dispersion medium. In the formation area 60 supplied with the binder solution 4, the particles of the stacked molding powder 1 are bonded to each other to obtain Figure 6 The bonding layer 41 shown. In the bonding layer 41, particles of the laminated modeling powder 1 are bonded to each other by a binder, and have a shape retention property to a degree that the particles are not damaged by their own weight.

[0048] In addition, the adhesive layer 41 may be heated simultaneously with or after the supply of the adhesive solution 4. This promotes the volatilization of the solvent and the dispersion medium contained in the adhesive solution 4, and promotes the bonding of the particles caused by the curing or hardening of the adhesive. In addition, when the adhesive contains a photocurable resin or an ultraviolet curable resin, light irradiation or ultraviolet irradiation may be performed instead of heating or together with heating.

[0049] The heating temperature is not particularly limited, but is preferably 50° C. to 250° C., more preferably 70° C. to 200° C. This allows sufficient heat to be applied to the adhesive layer 41 and sufficiently promotes volatilization of the solvent or dispersion medium.

[0050] The binder solution 4 is not particularly limited as long as it is a liquid having a component that can bind the particles of the laminated molding powder 1 to each other. As an example, as a solvent containing the binder solution 4, water, alcohols, ketones, carboxylates, etc. can be cited, and a mixed liquid containing at least one of them can also be used. Among them, water is preferably used as a solvent. The binder solution 4 containing water can reduce the environmental load compared to the case of containing an organic solvent.

[0051] The water content in the binder solution 4 is preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more. This can sufficiently increase the water content in the binder solution 4 and reduce the environmental load when the binder solution 4 is dried or discarded.

[0052] Examples of the binder contained in the binder solution 4 include fatty acids, paraffin wax, microcrystalline wax, polyethylene, polypropylene, polystyrene, acrylic resins, polyamide resins, polyesters, stearic acid, polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), polyethylene glycol (PEG), polyurethane resins, epoxy resins, vinyl resins, unsaturated polyester resins, and phenolic resins.

[0053] Among them, polyvinyl alcohol (PVA) or polyvinyl pyrrolidone (PVP) is preferably used as the binder. The binder solution 4 containing these binders has a moderate affinity and viscosity for the laminated molding powder 1 and has good adhesion. Therefore, such a binder solution 4 helps to manufacture a laminated molding body 6 with particularly good surface accuracy.

[0054] Furthermore, any additives may be added to the binder solution 4. Examples of the additives include a viscosity modifier, a surfactant, a moisturizer, a stabilizer, a defoaming agent, a crosslinking agent, and an antioxidant.

[0055] The concentration of the binder in the binder solution 4 is preferably 0.1 mass % or more and 20.0 mass % or less, more preferably 1.0 mass % or more and 15.0 mass % or less, and further preferably 5.0 mass % or more and 12.0 mass % or less. Thus, the viscosity of the binder solution 4 can be optimized, and sufficient bonding strength between the particles of the powder 1 for laminated modeling can be ensured.

[0056] The surface tension of the binder solution 4 is preferably set to 20 mN / m or more and 40 mN / m or less, more preferably set to 20 mN / m or more and 35 mN / m or less, and further preferably set to 20 mN / m or more and 30 mN / m or less. Thus, the driving force of penetration due to the capillary phenomenon is appropriately applied to the binder solution 4 in the powder layer 31. As a result, the penetration speed of the binder solution 4 in the powder layer 31 can be sufficiently increased.

[0057] In addition, if the surface tension of the binder solution 4 is lower than the lower limit, the driving force of penetration due to the capillary phenomenon does not sufficiently act on the binder solution 4 supplied to the powder layer 31. Therefore, the penetration rate may not be sufficiently increased. On the other hand, if the surface tension of the binder solution 4 exceeds the upper limit, the surface tension becomes excessive, so that the droplets of the binder solution 4 tend to sphericalize. Therefore, the binder solution 4 may become difficult to penetrate into the powder layer 31.

[0058] The surface tension of the binder solution 4 is measured using a surface tensiometer. Examples of the surface tensiometer include a surface tensiometer CBVP-Z manufactured by Kyowa Interface Science Co., Ltd.

[0059] 1.4. Repeating process

[0060] In the repetition step S106, the powder layer forming step S102 and the binder solution supplying step S104 are repeated one or more times until the laminated body formed by laminating a plurality of adhesive layers 41 has a predetermined shape. That is, these steps are performed twice or more in total. Fig.10 The three-dimensional stacked structure 6 is shown.

[0061] Specifically, first, Figure 7 As shown, in Figure 6 A new powder layer 31 is formed on the bonding layer 41 shown. Figure 8 As shown, the binder solution 4 is supplied to the formation area 60 in the newly formed powder layer 31. Thus, Fig. 9 The second adhesive layer 41 shown. By repeating these operations, a Fig.10 The stacked shaped body 6 is shown.

[0062] In addition, the laminated molding powder 1 in the powder layer 31 that does not constitute the bonding layer 41 is recovered and reused as needed, that is, it is provided again for the production of the laminated molding body 6.

[0063] 1.5. Method for producing metal sintered body

[0064] A metal sintered body is obtained by subjecting the stacked shaped body 6 to a sintering treatment. In the sintering treatment, the stacked shaped body 6 is heated to cause a sintering reaction.

[0065] The sintering temperature varies depending on the constituent material and particle size of the laminated modeling powder 1, but is preferably 980° C. to 1450° C., more preferably 1050° C. to 1350° C. The sintering time is preferably 0.2 hours to 7 hours, more preferably 1 hour to 6 hours.

[0066] The atmosphere for the sintering treatment may be, for example, a reducing atmosphere such as hydrogen, an inert atmosphere such as nitrogen or argon, or a reduced pressure atmosphere obtained by reducing the pressure of these atmospheres. The pressure of the reduced pressure atmosphere is not particularly limited as long as it is less than normal pressure (100 kPa), but is preferably 10 kPa or less, and more preferably 1 kPa or less.

[0067] In addition, when the sintering treatment performed under the above conditions is regarded as "main sintering", the stacked molded body 6 may be subjected to "temporary sintering" or "degreasing" as a pre-treatment equivalent to the main sintering, as required. In this way, at least a part of the binder contained in the stacked molded body 6 can be removed, or a part of it can be caused to undergo a sintering reaction. In this way, undesirable deformation, etc., can be suppressed during the main sintering.

[0068] The temperature of temporary sintering and degreasing is not particularly limited as long as it is a temperature at which the metal powder is not completely sintered, and is preferably 100°C or more and 500°C or less, and more preferably 150°C or more and 300°C or less. In addition, the time of temporary sintering and degreasing is preferably 5 minutes or more within the temperature range, more preferably 10 minutes or more and 120 minutes or less, and further preferably 20 minutes or more and 60 minutes or less. The atmosphere of temporary sintering and degreasing can include, for example, an air atmosphere, an inert atmosphere such as nitrogen and argon, or a reduced pressure atmosphere in which these atmospheres are reduced in pressure.

[0069] The metal sintered body obtained in the above manner can be used as a material for constituting, for example, automobile parts, bicycle parts, railway vehicle parts, ship parts, aircraft parts, transportation equipment parts such as space conveyor parts, electronic equipment parts such as personal computer parts, portable phone terminal parts, tablet terminal parts, and wearable terminal parts, electrical equipment parts such as refrigerators, washing machines, and air conditioners, machine parts such as machine tools and semiconductor manufacturing equipment, factory parts such as nuclear power plants, thermal power plants, hydroelectric power plants, refineries, and chemical complexes, watch parts, metal tableware, jewelry, and decorative items such as eyeglass frames.

[0070] 2. Layering modeling powder

[0071] Next, the laminated modeling powder according to the embodiment will be described.

[0072] Fig.11 It is a cross-sectional view schematically showing the powder for laminated modeling according to the embodiment.

[0073] The laminated modeling powder 1 according to the present embodiment is a powder used for producing the laminated modeling body 6 by the aforementioned binder jetting method, for example.

[0074] Fig.11 The laminated modeling powder 1 shown has a plurality of surface-covered particles 13, which include metal particles 11 made of a metal material and a coating 12 covering the surface of the metal particles 11. The coating 12 includes a compound derived from a coupling agent having an amino group. In addition, the coating 12 preferably covers the entire surface of the metal particle 11, but there may be an uncovered portion.

[0075] Metal particles

[0076] The metal material constituting the metal particles 11 is not particularly limited, and may be any material as long as it is a sinterable metal material, and examples thereof include single substances such as Fe, Ni, Co, and Ti, or alloys and intermetallic compounds containing these substances as main components.

[0077] The metal material is preferably an Fe-based metal material. The Fe-based metal material refers to a metal material having an Fe content of more than 50% by atomic ratio. The Fe-based metal material is easily available and can produce a metal sintered body with excellent mechanical properties.

[0078] Examples of Fe-based metal materials include stainless steels such as ferrite stainless steel, austenite stainless steel, martensite stainless steel, precipitation hardening stainless steel, and austenite-ferrite (two-phase) stainless steel, low carbon steel, carbon steel, heat-resistant steel, die steel, high-speed tool steel, Fe-Ni alloy, and Fe-Ni-Co alloy.

[0079] Among them, Fe-based metal materials preferably use stainless steel. Stainless steel is a type of steel with excellent mechanical strength and corrosion resistance. Therefore, by using the laminated molding powder 1 composed of stainless steel, a metal sintered body with excellent mechanical strength and corrosion resistance and high shape accuracy can be effectively manufactured.

[0080] Examples of austenitic stainless steel include SUS301, SUS301L, SUS301J1, SUS302B, SUS303, SUS304, SUS304Cu, SUS304L, SUS304N1, SUS304N2, SUS304LN, SUS304J1, SUS304J2, SUS305, SUS309S, SUS310S, SUS312L, and SUS315 J1, SUS315J2, SUS316, SUS316L, SUS316N, SUS316LN, SUS316Ti, SUS316J1, SUS316J1L, SUS317, SUS317L, SUS317LN, SUS317J1, SUS317J2, SUS836L, SUS890L, SUS321, SUS347, SUSXM7, SUSXM15J1, etc.

[0081] Examples of the ferrite-based stainless steel include SUS405, SUS410L, SUS429, SUS430, SUS430LX, SUS430J1L, SUS434, SUS436L, SUS436J1L, SUS445J1, SUS445J2, SUS444, SUS447J1, and SUS XM27.

[0082] Examples of martensitic stainless steel include SUS403, SUS410, SUS410S, SUS420J1, SUS420J2, and SUS440A.

[0083] Examples of precipitation-hardening stainless steels include SUS630 and SUS631.

[0084] Examples of austenite-ferrite (two-phase) stainless steel include SUS329J1, SUS329J3L, and SUS329J4L.

[0085] In addition, the above-mentioned symbols are material symbols based on JIS standards. The types of stainless steel in this specification are distinguished by the above-mentioned material symbols.

[0086] The stacked molding body 6 may also be manufactured using two or more stacked molding powders 1 composed of different types of metal materials. For example, the stacked molding body 6 may be divided into two parts, one of which is made of the stacked molding powder 1 composed of the first metal material, and the other part is made of the stacked molding powder 1 composed of the second metal material.

[0087] 2.2. Lamination

[0088] The coating 12 is formed by a reaction between a coupling agent having an amino group or an epoxy group and the surface of the metal particle 11. Therefore, the coating 12 contains a compound derived from the coupling agent having an amino group or an epoxy group and exhibits properties derived from the amino group or the epoxy group.

[0089] Examples of the coupling agent include compounds having an amino group or an epoxy group and a hydrolyzable group, and specific examples thereof include a silane coupling agent, a titanium coupling agent, and a zirconium coupling agent.

[0090] The following chemical formula is an example of the molecular structure of the silane coupling agent.

[0091]

[0092] In the above formula, X is a functional group, such as an amino group or an epoxy group. Y is a spacer group, and OR is a hydrolyzable group. In addition, R is, for example, a methyl group, an ethyl group, or the like.

[0093] The hydrolyzable group is, for example, an alkoxy group or a halogen group, and generates silanol by hydrolysis. The silanol reacts with the hydroxyl group generated on the surface of the metal particle to generate a compound derived from the coupling agent on the surface of the metal particle.

[0094] The coupling agent may contain at least one hydrolyzable group, preferably two or more, and more preferably three hydrolyzable groups as shown in the above formula. The coupling agent containing three hydrolyzable groups reacts with three hydroxyl groups generated on the surface of the metal particles. Therefore, the coating 12 from the coupling agent has good adhesion to the metal particles 11. In addition, the coupling agent containing three hydrolyzable groups also has excellent film-forming properties, so a coating 12 with excellent continuity can be obtained. Such a coating 12 helps to further improve the fluidity of the powder 1 for laminated modeling.

[0095] Both the amino group and the epoxy group have moderate hydrophilicity. That is, although the amino group and the epoxy group are not highly hydrophobic, they are not extremely hydrophilic. Therefore, if the coating 12 is endowed with an amino group or an epoxy group, the coating 12 is endowed with moderate hydrophilicity. Thus, even if the binder solution 4 is aqueous, the affinity between the powder layer 31 and the binder solution 4 can be improved. As a result, the binder solution 4 can be rapidly infiltrated into the powder layer 31, thereby avoiding a reduction in the supply speed of the binder solution 4 and suppressing uneven penetration range.

[0096] The spacer Y is a single bond or a divalent linking group, for example, a group including an alkylene group, a cycloalkylene group, an arylene group, an aralkylene group, etc. They have hydrophobicity derived from hydrocarbons and impart hydrophobicity to the coating 12. As a result, the coating 12 is not easy to absorb moisture even in a humid environment, so that the laminated modeling powder 1 whose fluidity is not easily reduced can be realized.

[0097] The spacer Y is particularly preferably an alkylene group. Thus, while suppressing the bulk height of the coupling agent molecule, a compound with moderate hydrophobicity is obtained, thereby imparting uniform and moderate hydrophobicity to the film 12. In addition, the linking group may be unsubstituted or may be substituted with a substituent. In addition, the spacer Y may also include other structures, such as oxygen atoms, sulfur atoms, etc.

[0098] The number of carbon atoms of the spacer Y is preferably 1 or more and 18 or less, more preferably 2 or more and 10 or less, further preferably 3 or more and 8 or less, and particularly preferably 3 or more and 6 or less. The number of carbon atoms of the spacer Y affects the hydrophobicity of the compound from the coupling agent. Therefore, if the number of carbon atoms of the spacer Y is within the above range, the balance between the hydrophilicity based on the amino group or epoxy group and the hydrophobicity based on the spacer Y becomes particularly good. As a result, even if the binder solution 4 is aqueous, a laminated modeling powder 1 that can form a powder layer 31 that achieves rapid permeability is obtained.

[0099] Examples of the coupling agent having an amino group include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltriisopropoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminoisobutyldimethylmethoxysilane, N-(2-aminoethyl)-3-aminoisobutylmethyldimethoxysilane, (aminoethylaminomethyl)phenethyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropylsilanetriol, and N-(2-aminoethyl)-3-aminopropyl trimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriisopropoxysilane, N-(6-aminohexyl)-3-aminomethyltrimethoxysilane, N-(6-aminohexyl)-3-aminomethyltriethoxysilane, N-2-(aminoethyl)-8-aminooctyltrimethoxysilane, N-(2-aminoethyl)-11-aminoundecyltrimethoxysilane, N-3-[amino(polyoxypropylene)]aminopropyltrimethoxysilane, 3-ureidopropyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-benzyl-3-aminopropyltrimethoxysilane, N-vinylbenzyl-3-aminopropyltriethoxysilane, etc.

[0100] Among them, it is preferred to use a coupling agent containing a secondary amine. The secondary amine is contained in the spacer Y, for example, and acts to alleviate the hydrophobicity of the spacer Y. Therefore, the compound derived from the coupling agent containing a secondary amine can realize a coating 12 with better affinity with the aqueous binder solution 4.

[0101] Furthermore, it is more preferable to use a coupling agent containing both a primary amine and a secondary amine. This can realize a coating film 12 having particularly excellent affinity with the aqueous binder solution 4 .

[0102] Examples of the coupling agent having an epoxy group include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane.

[0103] The average thickness of the coating 12 is not particularly limited, but is preferably 100 nm or less, more preferably 0.5 nm or more and 50 nm or less, and further preferably 1 nm or more and 10 nm or less. Thus, the required film thickness of the coating 12 can be ensured.

[0104] The average thickness of the coating 12 can be determined, for example, by qualitative and quantitative analysis in the depth direction using X-ray photoelectron spectroscopy and ion sputtering. Specifically, the concentration of the component from the coupling agent is investigated along the depth direction. And the area where the concentration of the component from the coupling agent is relatively high is taken as the average thickness of the coating 12. Specifically, when the concentration changes near the boundary between the coating 12 and the metal particle 11, half of the change in concentration, that is, the position corresponding to the midpoint between the concentration on the coating 12 side and the concentration on the metal particle 11 side is regarded as the boundary, and the thickness closer to the surface side than the boundary is taken as the average thickness of the coating 12.

[0105] In addition, the coating 12 may be a multilayer film formed by stacking the molecules of the aforementioned compound in multiple layers, for example, 2 or more layers and 10 or less layers, but is preferably a monomolecular film based on the aforementioned compound. In the coating 12 as a monomolecular film, its thickness can be minimized. As a result, when the stacked molded body 6 is produced, a stacked molded body 6 with a low occupancy rate of the coating 12 and a high occupancy rate of the metal particles 11 can be obtained. Such a stacked molded body 6 is useful in obtaining a metal sintered body with high shape accuracy, for example, because the shrinkage rate is suppressed when it is provided for sintering treatment.

[0106] In addition, a monomolecular film can be formed by utilizing the self-organization of the coupling agent. Since the coupling agent is densely arranged on the surface of the metal particles 11, a monomolecular film can be formed efficiently.

[0107] Whether or not the coating 12 is a monomolecular film can be evaluated as being a monomolecular film if, for example, the average thickness of the coating 12 measured by the above-described method is equal to or smaller than the molecular size of the coupling agent.

[0108] In addition, the coating 12 preferably contains any component other than the above-mentioned compound. However, in this case, from the viewpoint of reliably obtaining the above-mentioned effect, the mass ratio of the above-mentioned compound is preferably greater than 50%, more preferably greater than 70%, and further preferably greater than 90%.

[0109] 2.3. Various properties of powders for laminated modeling

[0110] Next, various characteristics of the powder for lamination modeling 1 will be described.

[0111] 2.3.1. Water penetration time

[0112] The powder layer is formed using the laminated modeling powder 1 according to the present embodiment. The hydrophilicity can be quantitatively evaluated by measuring the time it takes for water to penetrate the powder layer. The water penetration time is measured as follows.

[0113] First, the powder 1 for stacking modeling added to the container is pressed to form a powder layer in such a way that the relative density becomes 51%. The relative density of the powder layer is calculated based on the volume obtained from the area and thickness of the powder layer and the mass of the powder layer. In addition, the size of the formation range of the powder layer is 5 mm or more × 5 mm or more, and the thickness of the powder layer is 5 mm or more. Next, 40 μL of water is supplied to the powder layer as water droplets. Pure water is used as water. Then, starting from the time of supply, the time elapsed until all the supplied water penetrates into the powder layer is measured as the water penetration time.

[0114] In the above-mentioned powder layer formed using the laminated molding powder 1 involved in this embodiment, the water penetration time is preferably 10.00 seconds or less, more preferably 5.00 seconds or less, and further preferably 2.00 seconds or less. If the water penetration time is within this range, a powder layer 31 with a sufficiently large penetration rate of the aqueous binder solution 4 is obtained. In such a powder layer 31, even if the supply rate of the binder solution 4 is not slowed down, the aqueous binder solution 4 can be made to penetrate into the target range. Therefore, a laminated molding body with a high surface area can be effectively manufactured.

[0115] In addition, the water penetration time is also related to the oxidation of the laminated modeling powder 1 caused by water, the decrease in fluidity of the laminated modeling powder 1 caused by water adsorption, etc. Therefore, from the viewpoint of suppressing oxidation and decrease in fluidity caused by water, the water penetration time is preferably 0.01 seconds or more, more preferably 0.05 seconds or more, and further preferably 0.10 seconds or more.

[0116] If the water penetration time exceeds the upper limit, the aqueous binder solution 4 cannot be penetrated into the target range in the powder layer 31, or the supply rate of the binder solution 4 cannot be increased. On the other hand, if the water penetration time is lower than the lower limit, the filling property of the laminated modeling powder 1 in the powder layer 31 is reduced, or the laminated modeling powder 1 may be modified by oxidation.

[0117] 2.3.2. Infrared spectroscopic analysis

[0118] The laminated modeling powder 1 involved in this embodiment can evaluate the permeability of the aqueous binder solution 4 by providing it for infrared spectroscopic analysis. Specifically, first, the laminated modeling powder 1 is provided for infrared spectroscopic analysis to obtain an infrared absorption spectrum. A Fourier transform infrared spectrometer is used in the infrared spectroscopic analysis. In addition, the ATR method is particularly preferably used. Then, the intensity of each peak P1 from the siloxane bond (Si-O bond), the peak P2 from the amino group (NH2), and the peak P3 from the epoxy group (epoxy ring antisymmetric stretching) in the infrared absorption spectrum is obtained.

[0119] The peak wave number of peak P1 is between 1140 and 1120 cm -1 The peak wave number of peak P2 is between 1695 and 1650 cm -1 The peak wave number of peak P3 is between 920 and 910 cm -1 .

[0120] In the powder for laminated modeling 1 according to the present embodiment, the acquired infrared absorption spectrum has peaks P1 and P2 or peaks P1 and P3.

[0121] Fig.12 This is an example of an infrared absorption spectrum obtained from the powder 1 for laminated modeling when the powder 1 for laminated modeling has an amino group.

[0122] When the laminate modeling powder 1 has an amino group, Fig.12 The intensity of the peak P2 shown is preferably 5% or more of the intensity of the peak P1, and more preferably 10% or more. When the peaks P1 and P2 satisfy such an intensity ratio, the presence ratio of the amino group on the surface of the layered modeling powder 1 can be sufficiently increased. As a result, the layered modeling powder 1 that can form the powder layer 31 with a particularly optimized water penetration rate is obtained.

[0123] Furthermore, from the viewpoint of ensuring a sufficient ratio of siloxane bonds to obtain the adhesion strength of the coating 12 , the upper limit of the intensity of the peak P2 is preferably 70% or less, more preferably 50% or less, and even more preferably 40% or less.

[0124] In addition, if the intensity of the peak P2 is lower than the lower limit, when the powder layer 31 is formed using the laminated modeling powder 1, the water penetration rate in the powder layer 31 may not be sufficiently increased. On the other hand, if the intensity of the peak P2 exceeds the upper limit, the siloxane bonds are relatively insufficient, and the adhesion between the coating 12 and the metal particles 11 may be insufficient.

[0125] Fig.13 This is an example of an infrared absorption spectrum obtained from the laminated modeling powder 1 when the laminated modeling powder 1 has an epoxy group.

[0126] When the laminated modeling powder 1 has an epoxy group, the intensity of the peak P3 is preferably 5% or more of the intensity of the peak P1, and more preferably 10% or more. When the peaks P1 and P3 satisfy such an intensity ratio, the presence ratio of the epoxy group can be sufficiently increased on the surface of the laminated modeling powder 1. As a result, the laminated modeling powder 1 that can form the powder layer 31 with a particularly optimized water penetration rate is obtained.

[0127] From the viewpoint of ensuring a sufficient ratio of siloxane bonds to obtain the adhesion strength of the coating 12 , the upper limit of the intensity of the peak P3 is preferably 70% or less, more preferably 50% or less, and even more preferably 40% or less.

[0128] In addition, if the intensity of the peak P3 is lower than the lower limit, when the powder layer 31 is formed using the laminated modeling powder 1, the water penetration rate in the powder layer 31 may not be sufficiently increased. On the other hand, if the intensity of the peak P3 exceeds the upper limit, the siloxane bonds are relatively insufficient, and the adhesion between the coating 12 and the metal particles 11 may be insufficient.

[0129] 2.3.3. Coverage

[0130] The ratio of the area covered by the coating 12 to the entire surface of the metal particle 11 is referred to as "coverage". In the laminated modeling powder 1 involved in the present embodiment, the coverage of the coating 12 is preferably 10% or more and 150% or less, more preferably 20% or more and 90% or less, and further preferably 30% or more and 80% or less. Thus, even without slowing down the supply speed of the binder solution 4, it is possible to obtain a laminated modeling powder 1 that can form a powder layer 31 that allows the aqueous binder solution 4 to penetrate into the target range. In addition, at the same time, when a portion of the surface of the metal particle 11 is exposed, the metal particle 11 can enjoy a high affinity with the aqueous binder solution 4, so the penetration rate can be further increased. As a result, a laminated modeling body 6 with a high surface area can be manufactured more efficiently.

[0131] If the coverage is lower than the lower limit, the fluidity of the laminated modeling powder 1 may be reduced in a humid environment. On the other hand, if the coverage exceeds the upper limit, the hydrophobicity of the coating 12 becomes high depending on the molecular structure of the coupling agent, and the penetration rate of the aqueous binder solution 4 into the powder layer 31 may be reduced. In addition, the state where the coverage exceeds 100% means that at least two molecules of the compound derived from the coupling agent overlap in the thickness direction on at least a part of the surface of the metal particle 11.

[0132] The coverage of the coating 12 can be calculated based on the amount of the coating 12, the amount of the metal particles 11, the minimum coverage area of ​​the coupling agent, and the specific surface area of ​​the metal particles 11. The amount of the coating 12 can be calculated based on the concentration of the constituent elements of the coupling agent by, for example, performing qualitative and quantitative analysis on the powder 1 for stacking modeling based on X-ray photoelectron spectroscopy. For example, when the coupling agent is a silane coupling agent, the amount of the compound constituting the coating 12 can be calculated based on the Si concentration. In addition, the minimum coverage area of ​​the coupling agent can be obtained from the manufacturer, etc. according to the type of coupling agent. The specific surface area of ​​the metal particles 11 is measured using a specific surface area measuring device after removing the coating 12 from the powder 1 for stacking modeling, for example, using a reagent. As a specific surface area measuring device, for example, a BET-type specific surface area measuring device HM1201-010 manufactured by MOUNTECH Co., Ltd. can be cited.

[0133] 2.3.4. Particle size distribution

[0134] For the laminated modeling powder 1 involved in this embodiment, when the particle size distribution is obtained on a volume basis by a laser diffraction particle size distribution measuring device, the particle size when the accumulation of frequency from the small diameter side is 50% is set as D50. As a measuring device for particle size distribution, for example, Microtrac and HRA9320-X100 manufactured by Nikkiso Co., Ltd. can be cited.

[0135] The particle size D50 (average particle size) of the layered modeling powder 1 is preferably 1.0 μm or more and 15.0 μm or less, more preferably 3.0 μm or more and 12.0 μm or less, and further preferably 4.0 μm or more and 10.0 μm or less. Thus, the layered modeling powder 1 capable of manufacturing a layered modeling body 6 having excellent sinterability is obtained. In addition, the layered modeling powder 1 capable of forming a powder layer 31 having excellent fluidity and a high filling degree is obtained.

[0136] In addition, if the particle size D50 is lower than the lower limit, the particles of the laminated modeling powder 1 may be easily agglomerated. If agglomeration occurs, the fluidity of the laminated modeling powder 1 decreases, and the density of the metal sintered body may decrease. On the other hand, if the particle size D50 exceeds the upper limit, the sinterability of the laminated modeling powder 1 decreases, and when a metal sintered body is obtained from the laminated modeling body 6, the density of the metal sintered body may decrease.

[0137] 2.3.5. Water contact angle

[0138] The contact angle of water measured when the layered modeling powder 1 according to the present embodiment is spread in a layer is preferably 80° to 125°, more preferably 85° to 120°, and even more preferably 90° to 110°.

[0139] The laminated modeling powder 1 having a water contact angle within such a range can be considered to have a particularly good balance between hydrophilicity and hydrophobicity. Therefore, by using such a laminated modeling powder 1, even without slowing down the supply speed of the binder solution 4, it is possible to form a powder layer 31 that allows the aqueous binder solution 4 to penetrate into the target range. Therefore, a laminated modeling body 6 with a high surface area can be efficiently manufactured. In addition, the laminated modeling powder 1 having a water contact angle within the above range suppresses the adsorption of water even in a humid environment and has excellent fluidity.

[0140] If the water contact angle is lower than the lower limit, water may cause oxidation, fluidity reduction, etc. On the other hand, if the water contact angle exceeds the upper limit, the penetration rate of the aqueous binder solution 4 may decrease due to the hydrophobicity of the coating 12.

[0141] The contact angle of water in the laminated modeling powder 1 can be measured according to the following steps. First, stick a double-sided tape on a flat surface. Then, spread the laminated modeling powder 1 on the double-sided tape. The double-sided tape is, for example, polyester tape No. 31B, 0.080 mm in total thickness, manufactured by Nitto Denko Corporation. Then, gently press the spread laminated modeling powder 1 with a plate-like component. Then, use an air blower to blow away the excess laminated modeling powder 1. Thus, a test body for contact angle measurement is obtained. As an air blower, for example, a manual air blower used for cleaning cameras, etc. can be cited. Then, the front end of the air blower is fixed at a position 3 cm away from the test body, and air is blown three times.

[0142] Next, the contact angle of water on the test body was measured by the θ / 2 method using a contact angle measuring device, DropMaster 500, manufactured by Kyowa Interface Science Co., Ltd. The measurement conditions were an air temperature of 25°C and a relative humidity of 50%±5%. In addition, the amount of water added was set to 3 μL, and the measurement was performed 5 seconds after the drop.

[0143] 2.3.6. Bulk density and tap density

[0144] The bulk density AD of the powder for laminated molding 1 according to the present embodiment is preferably 2.50 g / cm 3 Above and 3.70g / cm 3 Below, more preferably 2.70g / cm 3 Above and 3.60g / cm 3 Below, more preferably 3.00 g / cm 3 Above and 3.50g / cm 3If the bulk density is within the above range, good filling properties can be ensured even in the natural state. Thus, when the powder layer 31 is formed using the laminated molding powder 1, a powder layer 31 with a high filling rate can be formed. As a result, a dense laminated molding body 6 with high surface accuracy can be obtained, and a high-density and high-surface-accuracy metal sintered body can be finally manufactured using the laminated molding body.

[0145] The bulk density of the laminated modeling powder 1 is measured according to the apparent density measurement method of metal powder specified in JIS Z2504: 2012. In addition, the bulk density is preferably measured using a powder property evaluation device, Powder Tester (registered trademark) PT-X manufactured by Hosokawa Micron Co., Ltd. In addition, before the bulk density measurement, the laminated modeling powder 1 to be measured is preferably placed in an environment with a temperature of 25° C. and a relative humidity of 50% for more than 1 hour.

[0146] The tap density TD of the laminated modeling powder 1 is preferably 4.10 g / cm 3 Above and 4.80g / cm 3 Below, more preferably 4.20g / cm 3 Above and 4.70g / cm 3 Below, more preferably 4.30 g / cm 3 Above and 4.60g / cm 3 If the tap density is within the above range, a high filling rate can be obtained when the powder layer 31 is leveled by the molding table 23 or compressed by the roller 25. Thus, a dense and high-precision stacked molding body 6 can be obtained, and a high-density and high-precision metal sintered body can be finally manufactured using the compact.

[0147] The tap density of the laminated modeling powder 1 is measured by a powder property evaluation device, Powder Tester (registered trademark) PT-X manufactured by Hosokawa Micron Co., Ltd. In addition, before measuring the tap density, the laminated modeling powder 1 to be measured is preferably placed in an environment of 25° C. and 50% relative humidity for 1 hour or more.

[0148] In addition, the ratio of the tap density of the laminated modeling powder 1 to the bulk density is preferably 1.10 or more and 1.60 or less, more preferably 1.15 or more and 1.50 or less, and further preferably 1.20 or more and 1.40 or less. If the ratio is within the above range, the difference in filling rate between the laminated modeling powder 1 in a natural state and the laminated modeling powder 1 after vibration, load, etc. is applied can be reduced. Therefore, deformation of the laminated modeling body 6 caused by the difference in filling rate can be suppressed. As a result, a metal sintered body with high surface accuracy is obtained.

[0149] The ratio may be lower than the lower limit, but it may be difficult to stably produce the laminated molding powder 1 having such characteristics. On the other hand, if the ratio exceeds the upper limit, the difference in filling rate becomes large, which may cause deformation of the laminated molding body 6.

[0150] 3. Method for producing powder for laminated modeling

[0151] Next, a method for producing the powder for laminated modeling 1 will be described.

[0152] The powder for laminated modeling 1 is produced, for example, through a preparation step, a coupling agent reaction step, and a film forming step.

[0153] 3.1. Preparation process

[0154] In the preparation step, a metal powder containing metal particles 11 is prepared. The metal particles 11 can be manufactured by any method, but preferably a powder manufactured by an atomization method such as water atomization, gas atomization, and rotating water flow atomization, and more preferably a powder manufactured by water atomization or rotating water flow atomization. In the metal particles 11 manufactured by these methods, the surface is easily covered with hydroxyl groups from water. Therefore, the adhesion of the coating 12 can be improved, and even if the coating 12 is thin, the fluidity of the powder 1 for stacking modeling can be fully improved. As a result, a stacking modeling body 6 can be achieved in which the occupancy rate of the metal particles 11 is high compared to the coating 12 and the shrinkage rate during sintering is small.

[0155] Furthermore, if necessary, the metal powder may be subjected to a known pretreatment for generating hydroxyl groups on the surfaces of the metal particles 11 .

[0156] 3.2. Coupling agent reaction process

[0157] In the coupling agent reaction step, the coupling agent is reacted with the metal powder. Examples of such operations include: heating the chamber after adding both the metal particles 11 and the coupling agent into the chamber (method 1); spraying the coupling agent into the chamber while stirring the metal particles 11 after adding the metal particles 11 into the chamber (method 2); adding water, coupling agent, ammonia, sodium hydroxide or other alkaline solution to a primary alcohol such as methanol, ethanol, isopropanol, stirring, filtering and drying (method 3). The coupling agent is supplied by allowing the solution to stand in the chamber or spraying it into the chamber.

[0158] The amount of the coupling agent added is not particularly limited, but is preferably 0.01% by mass or more and 1.00% by mass or less, and more preferably 0.05% by mass or more and 0.50% by mass or less, based on the metal particles 11 .

[0159] 3.3. Film forming process

[0160] In the coating formation step, the metal particles 11 to which the coupling agent is attached are heated. Thus, the coating 12 is formed on the surface of the metal particles 11, and the laminated modeling powder 1 is obtained. In addition, the unreacted coupling agent can be removed by heating.

[0161] The heating temperature of the metal particles 11 to which the coupling agent is attached is not particularly limited, but is preferably 50°C or more and 300°C or less, more preferably 100°C or more and 250°C or less, and further preferably 120°C or more and 200°C or less. The heating time is preferably 10 minutes or more and 24 hours or less, more preferably 30 minutes or more and 10 hours or less, and further preferably 1 hour or more and 6 hours or less. In addition, the heating time is the duration of the above-mentioned heating temperature. As the atmosphere for the heat treatment, for example, an air atmosphere, an inert gas atmosphere, etc. can be cited.

[0162] In addition, at least one of the coupling agent reaction step and the film forming step is preferably carried out in a closed container, and both steps are more preferably carried out in a closed container. Thus, the modification and volatilization of the coupling agent can be suppressed. As a result, the reaction amount and adhesion density of the coupling agent can be appropriately controlled, and a film 12 with target characteristics can be formed in the end. In particular, amino and epoxy groups are prone to undesirable reactions when heated at high temperatures, so by treating in a closed container, a laminated modeling powder 1 with target characteristics can be effectively manufactured.

[0163] 4. Effects of the Implementation Methods

[0164] As described above, the laminated modeling powder 1 according to the embodiment is a laminated modeling powder used for manufacturing a laminated modeling body 6 by a binder jetting method, and includes metal particles 11 and a coating 12, the coating 12 being provided on the surface of the metal particles 11 and containing a compound derived from a coupling agent having an amino group or an epoxy group. Furthermore, when 40 μL of water is dropped into a powder layer formed by pressing the powder to a relative density of 51%, the time for water to penetrate the laminated modeling powder 1 is 10.00 seconds or less.

[0165] According to such a structure, even without slowing down the supply speed of the binder solution 4, it is possible to realize the laminated modeling powder 1 which can form the powder layer 31 that allows the aqueous binder solution 4 to penetrate into the target range. By using such a laminated modeling powder 1, a laminated modeling body 6 with a high surface area can be efficiently manufactured.

[0166] Furthermore, in the powder for laminated modeling 1 according to the above embodiment, the coupling agent may contain a secondary amine.

[0167] According to such a structure, it is possible to realize the coating film 12 having a better affinity with the aqueous binder solution 4 .

[0168] In addition, in the laminated modeling powder 1 according to the embodiment, the coupling agent may also have an amino group. In this case, when the laminated modeling powder 1 is subjected to infrared spectroscopic analysis, the infrared absorption spectrum obtained has a peak P1 derived from a siloxane bond and a peak P2 derived from an amino group, and the intensity of the peak P2 is 5% or more of the intensity of the peak P1.

[0169] According to such a structure, the abundance ratio of the amino group to the surface of the layered modeling powder 1 can be sufficiently increased. As a result, the layered modeling powder 1 capable of forming the powder layer 31 having a particularly optimized water permeation rate can be obtained.

[0170] In addition, in the laminated modeling powder 1 according to the embodiment, the coupling agent may also have an epoxy group. In this case, when the laminated modeling powder 1 is subjected to infrared spectroscopic analysis, the infrared absorption spectrum obtained has a peak P1 derived from a siloxane bond and a peak P3 derived from an epoxy group, and the intensity of the peak P3 is 5% or more of the intensity of the peak P1.

[0171] According to such a structure, the abundance ratio of the epoxy group to the surface of the layered modeling powder 1 can be sufficiently increased. As a result, the layered modeling powder 1 capable of forming the powder layer 31 having a particularly optimized water permeation rate can be obtained.

[0172] In the layered modeling powder 1 according to the above embodiment, the coverage of the coating 12 on the surface of the metal particle 11 is preferably 10% or more and 150% or less.

[0173] According to such a structure, even without slowing down the supply speed of the binder solution 4, the laminated molding powder 1 can form the powder layer 31 that allows the aqueous binder solution 4 to penetrate into the target range. In addition, at the same time, when a part of the surface of the metal particles 11 is exposed, the metal particles 11 can enjoy the high affinity with the aqueous binder solution 4, so the penetration speed can be further increased. As a result, the laminated molding body 6 with a high surface area can be manufactured more efficiently.

[0174] Furthermore, the laminated modeling body 6 according to the above embodiment includes the laminated modeling powder 1 according to the above embodiment and a binder for binding particles of the laminated modeling powder 1 to each other.

[0175] According to such a structure, a stacked shaped body 6 having a high surface area can be obtained.

[0176] The laminated molding powder and the laminated molding body of the present invention have been described above based on the illustrated embodiments, but the present invention is not limited thereto. For example, the laminated molding powder and the laminated molding body of the present invention may be provided with any additional components in the above embodiments.

[0177] Example

[0178] Next, specific examples of the present invention will be described.

[0179] 5. Manufacturing of powder for laminated modeling

[0180] First, metal powders for laminated modeling powders of samples No. 1 to 17 were prepared by water atomization. The material constituting the metal powders was precipitation hardening stainless steel SUS630 (17-4PH). Next, a coupling agent was used to form a coating on the obtained metal powders. In addition, the reaction of the coupling agent and the subsequent heat treatment were performed while the metal powders and the coupling agent were placed in a sealed container. Thus, laminated modeling powders were obtained.

[0181] Next, the average particle size (particle size D50) of the manufactured laminated modeling powder, the functional group of the coupling agent, the number of carbon atoms of the spacer, the compound of the coupling agent, the intensity ratio of peaks P2 and P3 to peak P1, the coverage of the coating, the contact angle of water, the bulk density, the tap density, and the water penetration time were measured. The measurement results are shown in Table 1.

[0182] In addition, the compounds shown in Table 1 are as follows.

[0183] Compound A-1: ​​3-aminopropyltrimethoxysilane

[0184] Compound A-2: N-(2-aminoethyl)-3-aminopropyltrimethoxysilane

[0185] Compound A-3: N-2-(aminoethyl)-8-aminooctyltrimethoxysilane

[0186] Compound A-4: 3-Glycidoxypropyltrimethoxysilane

[0187] Compound A-5: 3-Glycidoxypropyltriethoxysilane

[0188] Compound B-1: Propyltrimethoxysilane

[0189] Compound C-1: trimethoxy(11-pentafluorophenoxyundecyl)silane represented by the following formula (C-1):

[0190]

[0191] Compound C-2: Pentafluorophenyldimethylchlorosilane represented by the following formula (C-2):

[0192]

[0193] In Table 1, the powder for laminated modeling corresponding to the present invention is referred to as "Example", and the powder for laminated modeling not corresponding to the present invention is referred to as "Comparative Example".

[0194] 6. Evaluation of the filling properties of powder for laminated modeling

[0195] 50 g of the laminated modeling powder of each sample No. was subjected to a heat treatment at 200° C. for 24 hours in an atmospheric atmosphere. Next, the laminated modeling powder after the heat treatment was placed in a 50 mL screw-threaded vial. Next, the height from the bottom to the upper surface of the powder was measured while the screw-threaded vial was erected. Then, the filling property of the laminated modeling powder was relatively evaluated by comparing the measured height with the following evaluation criteria. The evaluation results are shown in Table 1.

[0196] A: Height less than 25mm (particularly high filling capacity)

[0197] B: Height more than 25mm and less than 30mm (slightly higher filling capacity)

[0198] C: Height over 30mm (low filling capacity)

[0199] 7. Evaluation of the surface accuracy of laminated moldings

[0200] First, a laminated molding body in the shape of a rectangular parallelepiped was prepared by a binder jetting method using the laminated molding powder of each sample No. The dimensions of the laminated molding body prepared were 40 mm in length, 20 mm in width, and 5 mm in thickness. The binder solution used was a PVP aqueous solution containing PVP at a concentration of 10 mass %, a humectant at a concentration of 12 mass %, and the remainder being pure water.

[0201] Next, the obtained stacked molded body is observed by a digital microscope having a function as a non-contact surface roughness measuring device. Next, the arithmetic mean roughness Ra of the surface of the stacked molded body is measured based on the observation results. Then, by comparing the measurement results with the following evaluation criteria, the surface accuracy of the stacked molded body is relatively evaluated. The evaluation results are shown in Table 1.

[0202] A: Arithmetic mean roughness Ra is less than 4.0μm (surface accuracy is particularly high)

[0203] B: Arithmetic mean roughness Ra exceeds 4.0μm and is less than 7.0μm (slightly higher surface accuracy)

[0204] C: Arithmetic mean roughness Ra exceeds 7.0 μm (low surface accuracy)

[0205]

Table 1

[0206]

[0207] As shown in Table 1, it can be seen that in each example, the filling property of the layered modeling powder is sufficiently high, and further, the layered modeling body produced using the layered modeling powder has high surface accuracy.

[0208] In contrast, the surface accuracy of the laminated modeling bodies produced using the laminated modeling powders of the comparative examples was low. Such a result is believed to be due to the affinity between the laminated modeling powders and the aqueous binder solution.

Claims

1. A powder for laminated modeling, characterized in that: Used in the manufacture of laminated molded bodies based on the binder jetting method, The laminated modeling powder comprises: Metal particles; and The coating is provided on the surface of the metal particles and contains a compound derived from a coupling agent having an amino group or an epoxy group, When 40 μL of water was dropped onto a powder layer formed by compacting the powder to a relative density of 51%, the time required for the water to penetrate was 10.00 seconds or less.

2. The powder for laminated modeling according to claim 1, wherein The coupling agent comprises a secondary amine.

3. The powder for laminated molding according to claim 1 or 2, wherein: The coupling agent has an amino group, When subjected to infrared spectroscopic analysis, the infrared absorption spectrum obtained has a peak P1 derived from a siloxane bond and a peak P2 derived from an amino group. The intensity of the peak P2 is 5% or more of the intensity of the peak P1.

4. The powder for laminated molding according to claim 1, wherein The coupling agent has an epoxy group, When subjected to infrared spectroscopic analysis, the infrared absorption spectrum obtained has a peak P1 derived from a siloxane bond and a peak P3 derived from an epoxy group. The intensity of the peak P3 is 5% or more of the intensity of the peak P1.

5. The powder for laminated modeling according to claim 1 or 2, wherein: The coverage of the coating on the surface of the metal particle is 10% or more and 150% or less.

6. A stacked shaped body, characterized in that: The stacked shaped body has: The powder for laminated molding according to claim 1 or 2; and The binder binds the particles of the laminated modeling powder to each other.

Citation Information

Patent Citations

  • Methods and systems for creating objects by solid freeform fabrication

    JP2006515813A